The Murray Friedman collection of Wendell Willkie material - Friedman, Murray, 1926-
Correspondence, memoranda of conversations, other memoranda, and newspaper clippings collected by Murray Friedman while preparing a doctoral dissertation on Willkie. Relates chiefly to the Republican National Convention (1940) that nominated Willkie for President.
Collection material in English.
Keywords: Willkie, Wendell L. -- 1892-1944.